From #Ferguson to #Ayotzinapa: Analyzing Differences in Domestic and Foreign Protest News Shared on Social Media. Issue 5 (3rd September 2018) - Kilgo, Danielle K.; Harlow, Summer; García-Perdomo, Victor; Salaverría, Ramón
Abstract : This study compares U.S. digital news coverage of recent foreign and domestic protests. Differences in coverage's framing, sourcing, and device emphases were analyzed for two cases: protests that erupted after the death of Michael Brown and protests demanding justice for the 43 missing students from Ayotzinapa, Mexico. Building on protest paradigm literature, content analysis results show that news articles that appeared on Facebook and Twitter emphasized legitimizing frames for foreign protests more than domestic protests. Foreign protests were framed with the spectacle frame more than domestic protests, which were more often portrayed as confrontational. Digitally native news organizations produced content that deviated from expected paradigmatic norms the most. In addition, this research examines the relationship between content and sharing on Facebook and Twitter. Implications of these findings within the theoretical framework of the protest paradigm are discussed.